What is history? Husserl, Heidegger, Benjamin, Foucault - Escudero Pérez, Alejandro (Revista de Filosofía, 2022)
After the crisis of the modern conception of history, one of the tasks of today’s philosophy is to restate the question “What is history?”. In this article, we will look for the elements to elaborate an answer to this question in some specific texts of Husserl, Heidegger, Benjamin, and Foucault. In the framework of an event ontology, the core of this proposal will consist of distinguishing between a formal a priori of history and a material a priori.
Keywords: history; a priori; past; understanding; world; event